PENGARUH NEGARA ASAL TERHADAP NIAT PEMBELIAN MELALUI CITRA MEREK OLEH KONSUMEN SEPATU DI KOTA BANDUNG - Fauziyyah, Salma; Dimyati, Mohamad; Suryaningsih, Ika Barokah (BISMA: Jurnal Bisnis dan Manajemen, 2018)
Today’s consumers are very critical in making choices for the shoes products by considering the intrinsic and extrinsic factors of the products which one of them is the country of origin of the product brand. The purpose of this study is to analyze the influence of country of origin on the purchase intention through brand image of the shoes products for the consumers in Bandung City. The population of this research is the shoes consumers in Bandung City. The sample consists of 125 respondents taken by purposive sampling approach. The method of analysis used in this study is Structural Equation Modeling (SEM). The results indicate that country of origin influences brand image, brand image influences purchase intention, but there is no direct influence of country of origin on purchase intention of the shoes product in Bandung City. Keywords: Country of Origin, Brand Image, Purchase Intention.